2017
DOI: 10.31219/osf.io/49898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Your Eyes Only? Discrepancies and Agreement Between Self- and Other-Reports of Personality From Age 14 to 29

Abstract: Do others perceive the personality changes that take place between the ages of 14 and 29 in a similar fashion as the aging person him-or herself? This cross-sectional study analyzed age trajectories in self-versus other-reported Big Five personality traits and in self-other agreement in a sample of more than 10,000 individuals from the myPersonality Project.Results for self-reported personality showed maturation effects (increases in extraversion, conscientiousness, openness to experience, and emotional stabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…59 It was also close to the agreement between self and other ratings among Facebook friends for personality traits. 60 Despite being very brief-a median of 10 words-the texts contained condensed, pertinent information. Our social judgment analysis showed that coders relied on cues such as regret, the number of risks listed for the last 12 months, and risk avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…59 It was also close to the agreement between self and other ratings among Facebook friends for personality traits. 60 Despite being very brief-a median of 10 words-the texts contained condensed, pertinent information. Our social judgment analysis showed that coders relied on cues such as regret, the number of risks listed for the last 12 months, and risk avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for self-other agreement to be higher on extraversion and conscientiousness has been replicated often both cross-sectionally (Connelly & Ones, 2010) and across development (Göllner et al, 2017, Luan et al, 2017. Cross-sectional self-other agreement has been shown to increase from adolescence to young adulthood, mirroring the maturity principle of personality development (Rohrer, Egloff, Kosinski, Stillwell, & Schmukle, 2018). However, there have been fewer studies specifically on self-other agreement on personality trait change, and to our knowledge no studies in older adulthood.…”
Section: Self-other Agreement On Personality Changementioning
confidence: 91%